Best Practice Approach for Assessment of Microchip-associated Tumors in Preclinical Safety Studies: Position of the Registry of Industrial Toxicology Animal-data (RITA). (October 2018) - Lapp, Stefanie; Bube, Axel; Colbatzky, Florian A.; Ernst, Heinrich; Kellner, Rupert; Nolte, Thomas; Rinke, Matthias
Microchip (passive radio-frequency identification device) implantation is a common and widely employed means of animal identification in laboratory animal facilities. However, these devices have been associated with tumors of the skin and subcutis in rodents. While microchip-associated tumors are rare, they pose a challenge for accurate diagnosis and documentation in preclinical toxicity studies. Documentation of these tumors should differentiate microchip-associated lesions with spontaneously occurring or test article–induced tumors. Standardizing criteria for microchip-associated lesions will aid the diagnostic process and allow for preclinical regulatory standardization. To this end, the Registry of Industrial Toxicology Animal-data have developed clear recommendations for diagnosis and documentation of microchip-associated lesions.